Usia, Pendapatan, dan Tingkat Keterlibatan Ayah pada Pengasuhan Anak (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2017)
Father involvement on child rearing is very important on child development. It contains of self-accomplishment on physic, cognition, and affection aspect. Father’s age and salary are important factors which connect to the quality of father involvement on child rearing. This research purpose is to know whether there is a correlation between father’s age and salary with the level of father involvement on child rearing. This research method is quantitative. There 60 fathers involved in this research as a subject. The statistic correlation technique for data analyzing is chi-square. The result shows that there is a correlation between father’s age with the level of father involvement on child rearing. And there is no correlation between father’s salary with the level of father involvement on child rearing. Keywords: involvement, father, child rearing